AUTHORSHIP CHARACTERISTIC IN SEKITAR PERPUSTAKAAN 1994-2003: A BIBLIOMETRIC STUDY - Tiew, W. S. (Malaysian Journal of Library and Information Science, 2006)
This bibliometric study attempts to explore the authorship characteristics in Sekitar Perpustakaan, one of the earliest library and information science (LIS) periodicals published by the National Library of Malaysia (PNM – Perpustakaan Negara Malaysia) since 1977. A total of 148 articles published in 20 issues of Sekitar Perpustakaan covering the period 1994-2003 were analyzed. Author characteristics such as name, gender, status, institutional affiliation, language preference of articles and authorship of articles were obtained, studied and analyzed. The findings reveals single-authored articles far outnumbered multi-authored articles at 79%; female contributors (65.74% or 71 authors) predominates male contributors (34.26% or 37 authors); middle-level professionals were the largest contributors of articles (59.3%); 83 (56%) of the articles published were in Bahasa Melayu, the national language, while 65 (44%) articles were in English; the top ranked contributor is Ding Choo Ming, Senior Research Fellow of Institute of the Malay World & Civilization, Universiti Kebangsaan Malaysia with nine contributions; and the most prolific institution is PNM with 41 contributing authors.